PERAN DAN STANDAR KOMPETENSI PENILIK - Harjanto, Endro (JIV-Jurnal Ilmiah Visi, 2006)
The topic discusses the role of assessors in NFE as education personnel. Main tasks of an assessors are controlling, evaluating, guiding, and reporting of activities of NFE. These tasks are vital to the quality of performance of educators and programs. An assessor should be a highly, self-motivated person, and s/he is expected to be able to analyze problems and formulate alternatives. In order to be able to accomplish the job, s/he posseses some comptencies which are knowledge of paedagogic and andragogic, be professional, has a pleasant personality, and be able to socialize or to communicate with society and participants.